2021
DOI: 10.1002/jso.26613
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative C‐reactive protein concentrations to predict infective complications following gastrectomy for cancer

Abstract: Background and Objectives: Gastrectomy for gastric cancer is associated with significant infective postoperative complications. C-reactive protein (CRP) is a useful biomarker in the early detection of infective complications following major abdominal surgery. This single-centre retrospective study aimed to determine the relationship between postoperative CRP levels and development of postoperative infective complications after gastrectomy.Methods: Daily postoperative CRP levels were analyzed to determine a CRP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 46 publications
0
12
0
2
Order By: Relevance
“…A meta-analysis of CRP [ 4 ] involving 7 cohort studies demonstrated a lower AUC (0.76) for predicting postsurgical infection complications when compared to NLR (0.84) in our meta-analysis. The AUC in the most recent study of CRP by Winsen M and colleagues was only 0.765 [ 30 ]. As for procalcitonin, the levels were insignificantly different between the infection and non-infection groups in spinal instrumentation surgery [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of CRP [ 4 ] involving 7 cohort studies demonstrated a lower AUC (0.76) for predicting postsurgical infection complications when compared to NLR (0.84) in our meta-analysis. The AUC in the most recent study of CRP by Winsen M and colleagues was only 0.765 [ 30 ]. As for procalcitonin, the levels were insignificantly different between the infection and non-infection groups in spinal instrumentation surgery [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have read with interest the article published by van Winsen et al 1 Although we believe it is a very interesting topic, we would like to offer the following points for your consideration.…”
Section: Postoperative C-reactive Protein Concentrations To Predict Infective Complications Of Gastric Cancermentioning
confidence: 99%
“…3 In addition, diseases like postoperative infection, cardiovascular disease, and cancer can cause elevated levels of CRP. 4,5 CRP was also used as a non-specific marker to diagnose notable COVID-19 for a time. 6 Therefore, methods of CRP sensing have aroused widespread interest in clinical trials.…”
Section: Introductionmentioning
confidence: 99%